Effects of upper gastrointestinal endoscopy on the cardiovascular system of asymptomatic middle-aged and elderly patients without heart disease - Mehmet S. ÜLGEN; Yüksel ATEŞ; Zeki SOYPAÇACI; Talat KELEŞ (Turkish Journal of Gastroenterology, 2019)
-